2001
DOI: 10.1021/ie000663p
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Stabilization of Water-in-Crude Oil Emulsions

Abstract: The mechanisms of stabilization of water-in-crude oil emulsions have been investigated by changing the solvent-solute interactions in crude oil. Diluting the original crude oil with varying amounts of heptane, which is a poor solvent for asphaltenes, changes the solvent-solute interactions, leading to flocculation of asphaltenes and thus changing the emulsion stability. The interactions between the water droplets in an emulsion system have been quantified by measuring the radial distribution function and there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 23 publications
1
55
0
6
Order By: Relevance
“…These emulsions need to be destroyed after oil has been produced out of the reservoirs to recover the oil. A great deal of studies of these emulsions can be found in the literature (3)(4)(5), together with studies of the effect of various demulsifiers (6)(7)(8)(9). To obtain oil-in-water emulsions or to break the already existing water-in-oil emulsions, watersoluble surfactants need to be added and can possibly affect the interfacial structure.…”
Section: Introductionmentioning
confidence: 99%
“…These emulsions need to be destroyed after oil has been produced out of the reservoirs to recover the oil. A great deal of studies of these emulsions can be found in the literature (3)(4)(5), together with studies of the effect of various demulsifiers (6)(7)(8)(9). To obtain oil-in-water emulsions or to break the already existing water-in-oil emulsions, watersoluble surfactants need to be added and can possibly affect the interfacial structure.…”
Section: Introductionmentioning
confidence: 99%
“…Most crude oils that contain asphaltenes and naphthenic acids, especially heavy crude oils form marine environments trend to form stable W/O emulsions, which are complex scattered systems (Kumar et al, 2001).…”
Section: Ionic Liquids As Demusifier Agentsmentioning
confidence: 99%
“…The presence of the demulsifier molecules at the oil-water interface favors the drainage of the thin liquid films between the approaching emulsified water drops. On the other hand, demulsifiers could also bridge water droplets and therefore lead to flocculation of the emulsified water droplets, enhancing coalescence and phase separation (Kumar et al, 2001;Liu et al, 2003;Rondon et al, 2008).…”
Section: Introductionmentioning
confidence: 99%